Participatory Leadership of The Principal in Improving Teacher Competence - Kemal, Isthifa; Arlita, Firmanda; Aktar, Salim (Journal for Lesson and Learning Studies, 2023)
Principal leadership affects the quality of a school. The principal plays an important role in the educational circle of a school, so it can be said to be the spearhead of the successful achievement of school goals. The purpose of this study was to analyze the participatory leadership role of school principals in improving competence. The research method used is qualitative research with the case study method. There were 34 informants in this study, consisting of school principals, teachers and administrators. Data collection technique is use triangulation. Data analysis techniques in data collection using techniques are editing, categories, data display and interpretation. The results of the study show that school principals carry out participatory leadership. Participatory leadership by school principals can improve teacher competency. Professional competence, the teacher understands the main tasks and functions. The teacher implements various strategies and ways of managing classes, and plans and utilizes various available learning resources. The teacher creates an atmosphere of familiarity with students, always communicates well with fellow educators, and communicates with parents about the learning progress of their students. The teacher sets a good role model for students, is consistent in dressing modestly, and speaks using kind and polite words. Therefore, the teacher is able to improve his quality, both the quality of professional, pedagogic, social and personality.